Termites - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Termites: biology and pest management. By M Pearce. 1998. ISBN 0 85199 130 0 Publishing Division CAB International Wallingford Oxon, OX10 8DE UK. Fax: +44 1491 833508 Email: cabi@cabi.org. http://www.agricta.org/Spore/spore74